Assessing Open Source Software Success in Learning Management Systems Context in Jordan: Applied Of an Integration of Technology Acceptance Model and Information Systems Success (International Journal of Scientific Research and Management (IJSRM), 2020)
The main purpose of this study is to depend on an integration of Technology Acceptance Model (TAM) and Information Systems Success (ISS) model that was altered to define the success variables of Open Source Software (OOS) based on Open-EMIS system that attaches to Education Ministry of Jordan by employees. The methodology of current study was built on quantitative approach with two waves of data collection (Pre and post- test). For test hypotheses purposes, the Structural Equation Model (SEM) was applied. Moreover, the added value of this research is to meet the poverty in literature engaged with OOS. It is also contributed at exploring how the Education Ministry of Jordan can reap benefits from Open-EMIS usage. The study disclosed perceived ease of use, perceived usefulness, service quality, system quality, information quality, user satisfaction and intention to use as important variables for influencing Open-EMIS usage; as important finding, the relationships between the variables in pre and post-phases do not differ significantly. Finally, the future work in OOS area is recommended to be conducted.